1986
DOI: 10.1038/ki.1986.158
|View full text |Cite
|
Sign up to set email alerts
|

The Goodpasture antigen in Alport's syndrome: Studies with a monoclonal antibody

Abstract: A mouse monoclonal antibody (MCA-P1), which recognizes an antigenic determinant in human glomerular basement membrane against which autoantibodies are directed in Goodpasture's syndrome, was used in indirect immunofluorescence studies to investigate glomerular basement membrane structure in Alport's syndrome. We found reduced or absent binding of MCA-P1 to glomerular and distal tubular basement membranes in renal biopsy tissue from ten patients with Alport's syndrome. Antiglomerular basement membrane antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…These findings suggest that the absent GBM antigen is related to the nephritogenic antigens(s) of Goodpasture's syndrome. Savage et al [12] have recently confirmed this finding, using a mouse mon oclonal antibody (MCA-PI) which recognizes the Good pasture's antigen. Using an indirect IF technique, they found reduced or absent binding of MCA-PI to glomeru lar and distal TBMs in renal biopsy tissue from 10 pa tients with Alport's syndrome.…”
Section: Discussionsupporting
confidence: 57%
“…These findings suggest that the absent GBM antigen is related to the nephritogenic antigens(s) of Goodpasture's syndrome. Savage et al [12] have recently confirmed this finding, using a mouse mon oclonal antibody (MCA-PI) which recognizes the Good pasture's antigen. Using an indirect IF technique, they found reduced or absent binding of MCA-PI to glomeru lar and distal TBMs in renal biopsy tissue from 10 pa tients with Alport's syndrome.…”
Section: Discussionsupporting
confidence: 57%
“…It is known that antibodies recognizing the Goodpasture antigen do not bind to the GBM ofmost patients with Alport's syndrome, a hereditary nephritis that is usually transmitted in an X-linked manner (43,44). The existence of the a5 chain of type IV collagen had not been suspected biochemically or immunologically, but its gene is located in the appropriate region of the X chromosome (10), and abnormalities ofthe COL4A5 gene have since been identified in 3 of 18 Alport kindreds (45).…”
Section: Discussionmentioning
confidence: 99%
“…Several determina tions of serum anti-GBM antibodies have been negative in all the patients. A possible explanation for this is vari ation in the quantity of immunoreactive auto-antigen in different patients with Alport's syndrome [10]. There may be considerable heterogeneity of inherited nephritis of the Alport type, and/or the degree of binding may reflect sex differences in the amount of antigen present in the basement membrane, since most patients with absent binding of Goodpasture serum were male in Sav age's study [10].…”
Section: Discussionmentioning
confidence: 99%